Role of hysteroscopy in the diagnostics of endometrium pathology and in the application of auxiliary reproductive technologies - Lutsky, Andrii; Kuzmina, Iryna; Lutska, Svetlana (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2023)
Abstract. The introduction of endoscopic technologies made it possible to significantly expand diagnostic possibilities and clarify the nature of intrauterine pathology when using assisted reproductive technologies. Hysteroscopy allows you to take material for examination from the uterine cavity, and also ensures the carrying out of this procedure for diagnostic purposes as much as possible. Treatment of infertility by hysteroscopy plays a very important role in restoring a woman's reproductive function. The aim of the study was to improve the diagnosis of endometrial pathology through the use of hysteroscopy and targeted biopsy in the restoration of fertility and the use of assisted reproductive technologies. Materials. A clinical and statistical analysis of the results of 88 operative hysteroscopies in patients with infertility, which were divided into two groups, was carried out. The first group included 80 patients (90.91 %) with genital and extragenital pathology. The second group included 8 patients (9.01 %) who did not have concomitant gynecological and extragenital pathology. Hysteroscopy was performed with the equipment and tools of the «KARL STORZ» company. Monopolar and bipolar coagulation was used for hemostasis. Taking into account that pathology of the uterine cavity and endometrial are frequent causes of impaired reproductive function, it was proposed to use hysteroscopy to restore reproductive function. The results. The condition of the mucous membrane of the uterus with the help of hysteroscopy was studied in all clinical observations, since this method of instrumental research allows primarily to examine and evaluate the structural features of the endocervix and endometrial. In observation groups I and II, hysteroscopy was performed in all 88 patients: group 1 in 80 patients (90.91%) with pathological changes of the uterine mucosa and group 2 – in 8 patients (9.01 %) without pathology of the uterine mucosa. At the same time, 4 (3.52 %) women of 2 groups were diagnosed with extragenital pathology, and gynecological pathology was eliminated. The most common were endometrial polyps, chronic endometritis, cervical canal stenosis, and synechiae in the uterine cavity. Endoscopic technologies have expanded the diagnostic capabilities of investigating intrauterine pathology at the stage of fertility restoration and preparation for in vitro fertilization (IVF) and overcoming the causes of infertility. Conclusions. Hysteroscopy with morphological examination of the endometrial remains the main method of diagnosing intrauterine pathology. The obtained data will help the clinician to make the correct diagnosis in a timely manner and develop optimal and individual patient management tactics.